Disseminated cerebral and spinal tuberculomas: rare cause of triparesis. (20th April 2013) - Verma, Rajesh; Bhandari, Aveg
Abstract : Tuberculosis continues to remain a significant public health problem in developing nations, causing substantial morbidity and mortality. Central nervous system (CNS) tuberculosis is frequently observed in endemic zones of tuberculosis including India. The emergence of infections like HIV and malnutrition ruined the public health measures to restrain tuberculosis in developing countries. The incidence of intraspinal tuberculomas is reported to be 0.2–5% among CNS tuberculomas. To date, only a few cases have been reported of mixed intraspinal and intracranial tuberculomas. The clinical outcome in CNS disseminated tuberculomas is not well described in the literature. With this view, we report a case of a 25-year-old woman who presented with neck pain, triparesis and bladder incontinence, which finally proved to be a case of multiple cerebral and spinal tuberculomas. The antitubercular treatment with steroids and other supportive measures resulted in good recovery.